Learning methods according to hadith: interactive perspectives in education - Muasmara, Ramli; Husti, Ilyas; Zamsiswaya, Zamsiswaya; Fibriyani, Nola (UIN Salatiga, 2025)
The learning methods currently used by educators are still not optimal in fostering students' understanding of the subject matter. This contributes to problems related to developing students' character and skills. This research examines learning methods based on the Prophet Muhammad's hadith by highlighting interactive educational perspectives. The Prophetic Hadiths not only provide spiritual and moral guidance but also contain pedagogical principles that are relevant to modern learning contexts. This research uses a descriptive qualitative approach through a literature review, collecting references from books, scientific articles, and theoretical documents related to curriculum innovation strategies. The research findings reveal that interactive methods modeled by the Prophet, such as question and answer, habituation, and discussion, can improve academic performance, build moral character, and develop students' practical skills. This research highlights the relevance of interactive learning methods in modern education, focusing on active student participation and addressing the challenges of contemporary educational needs, particularly 21st-century skills.